Effects of Humor in Health Communication: Experimental Evidence for Video Sequences Aiming to Increase the Willingness to Donate Organs - Baumeister, Rebecca; Fischer, Florian (Frontiers in Public Health, 2021)
Humor has been proven to provide support when dealing with fear-related aspects of life. Therefore, it might be a useful communication strategy for addressing the need for donated organs. We conducted an experimental study among university students in Germany (n = 236) aged about 25 years (M = 24.60, SD = 5.86) investigating the effects of four video sequences related to organ donation on the willingness to donate organs. Based on random allocation, each study participant received one video sequence. The video sequences were presented by either a prominent or non-prominent speaker and included either humorous or neutrally framed information related to organ donation. An online survey was conducted before and after the intervention. A follow-up to investigate long-term effects was conducted four to six weeks later. Overall, the four interventions led to high proportions of self-reported willingness to think about organ donation and talk about it with relatives and friends subsequent to the respective intervention. Appraisals beneficial to organ donation improved significantly only in the non-humorous interventions. It seems to be of little relevance whether the humorous message was communicated by a prominent or non-prominent person. However, future investigations should focus on sample populations with lower education, because they are less likely to possess an organ donor card and more likely to have lower levels of positive attitudes towards organ donation and may, therefore, show different results regarding the effectiveness of humorous interventions.